PEMBAHARUAN PEMIKIRAN MAHMUD YUNUS TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN PENDIDIKAN MODERN - Muhammad Abdulloh (Universitas Yudharta Pasuruan, 2020)
This article aims to examine and explain about the movement of the thinking of Mahmud Yunus thoughts on Islamic education. Mahmud Yunus is a figure of the renewal of Islamic education derived from Minagkabau. The idea of Mahmud Yunus in the field of Islamic education is generally strategic and is a pioneering work, in the sense that it has not been done by the Islamic education figures before. This type of research is literature research and data is derived from several secondary and tertiary literature related to the thought of Mahmud Yunus and its relevance to modern education. This study focused more on the attention and commitment of Mahmud Yunus to the development, improvement and development of Islamic education that can be seen further in some aspects of Islamic education thinking among others in terms of Islamic education, objectives, curriculum, teaching methods educators and institutional Islamic education.